Perlindungan Hukum Terhadap Hak Pemenang Lelang Atas Tanah : Legal Protection of Auction Winner's Rights Above Ground - Rudy, Irnawaty; Makkawaru, Zulkifli; Tira, Andi (Clavia, 2021)
Auction is the sale of goods that are open to the public with a written and/or verbal price offer that is increasing or decreasing to reach the highest price, which is preceded by the announcement of the auction. This study aims to determine the legal protection measures against the winner of the land auction. The research method used is empirical legal research by collecting systematic data, recording, interpreting, and critically analyzing facts or data as well as making reports and information on symptoms studied from various aspects to find conclusions. All data that has been obtained are then analyzed and described in a qualitative descriptive manner. The results showed that the auction rules were not implemented in practice. Makassar District Court Decision No. 278/Pdt.G/2018/Pn.Mks cancel the SHM owned by the Auction Winner because the SHM is manipulative. The lack of in-depth data analysis and the application of the rules of the auction procedure on Mortgage are the factors that cause the winner of the auction to lose his rights. One of the actions that can guarantee legal protection for the winner of the auction is through the courts. Where in this case, the auction winner can make the decision of the case his basis for demanding accountability for the parties involved in the auction process for the land object. Such as KPNL and BPN carry out administrative responsibility and the seller (Bank) compensates for all costs that the winner of the auction redeems in the auction process. Keywords: Auction, Dispute, Accountability